An overview of combined D‐2‐ and L‐2‐hydroxyglutaric aciduria: functional analysis of CIC variants. Issue 2 (13th December 2017) - Pop, Ana; Williams, Monique; Struys, Eduard A.; Monné, Magnus; Jansen, Erwin E. W.; De Grassi, Anna; Kanhai, Warsha A.; Scarcia, Pasquale; Ojeda, Matilde R. Fernandez; Porcelli, Vito; van Dooren, Silvy J. M.; Lennertz, Pascal; et al.
Abstract: Combined D‐2‐ and L‐2‐hydroxyglutaric aciduria (D/L‐2‐HGA) is a devastating neurometabolic disorder, usually lethal in the first years of life. Autosomal recessive mutations in the SLC25A1 gene, which encodes the mitochondrial citrate carrier (CIC), were previously detected in patients affected with combined D/L‐2‐HGA. We showed that transfection of deficient fibroblasts with wild‐type SLC25A1 restored citrate efflux and decreased intracellular 2‐hydroxyglutarate levels, confirming that deficient CIC is the cause of D/L‐2‐HGA. We developed and implemented a functional assay and applied it to all 17 missense variants detected in a total of 26 CIC‐deficient patients, including eight novel cases, showing reduced activities of varying degrees. In addition, we analyzed the importance of residues affected by these missense variants using our existing scoring system. This allowed not only a clinical and biochemical overview of the D/L‐2‐HGA patients but also phenotype–genotype correlation studies.